Are people’s lives in coal mining areas better than others? A Comparative Social Study in Two Regions in Tropical Rainforest Areas - Permana, Lies; Anggraeni, Ika; Nurrachmawati, Annisa (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The mining area expands to more than 5 million hectares zoned for coal concession in East Kalimantan. East Kalimantan is the one of province that exist in tropical rainforest areas. The mining coal covers most of the region of East Kalimantan, including Samarinda the capital city of the province and Kutai Kartanegara the region that has a bigger proportion of regional income from the mining coal activities. Furthermore, Kutai Kartanegara has a coal mining area wider than Samarinda due to the company's responsibility to contribute to its surrounding environment. Mining often leads to significant changes to a society's social and economic structure. Social equity requires that such changes enhance overall social well-being, including the availability of adequate infrastructure, health services, and education, rather than only benefiting a select few or particular parties. Objective : This study aims to compare the people’s welfare of those who live closest to the mining area in Samarinda City and Kutai Kartanegara Regency, including their socioeconomic status and accessibility to public facilities. Research Methods/ Implementation Methods : This was an observational study with a cross-sectional approach. Data was collected by survey with structured questionnaires in Samarinda city and Kutai Kartanegara regency which is close to the mining area. As much as 218 respondents were collected from four different areas in Samarinda and 232 respondents were collected from six different areas in Kutai Kartanegara. The samples were selected by accidental sampling of those living in the areas. The questionnaire created some questions about the respondent’s characters (age, sex, education level, monthly income, home ownership) and how have they accessed the public facility (market, school, public health centre) using four-choice answers (very hard, hard, easy and very easy). The data was analyzed using the Chi-square Test to identify whether there were statistically significant differences between each variable in Samarinda City and Kutai Kartanegara Regency. Results : The results showed that statistically there were different proportions between Samarinda City and Kutai Kartanegara Regency in terms of education level (p 0.034), monthly income (p 0.015), market accessibility (p 0.000), school accessibility (p 0.023), and public health centre accessibility (p 0.000). There is only one variable that has no difference in home ownership (p 0.777). Regarding home ownership, there is no difference between the respondents in Samarinda and Kutai Kartanegara. They have their own home in common, only 23.9% of people do not have their own home in Samarinda and 25% in Kutai Kartanegara. Conclusion/Lesson Learned : The study implies that there is inequality of welfare and public access, especially in Kutai Kartanegara Regency compared to Samarinda City. This may lead to differences in income and education levels. Accessing facilities that support equity will be more challenging when communities are located or live close to mining areas. Thus, the attention of local government and mining companies is needed for further development of welfare and access to public facilities in the future.